Diseño de sonido 3D para un videojuego en primera persona para PC en versión demo a través de la implementación de un motor de audio generador de banda sonora - Pacheco Salgado, Maricruz Coralía (2015)
The present project contemplates the design and implementation of a videogame soundtrack through the use of a 3D sound processing audio engine. Game programmer Juan Manosalvas developed a project for which the soundtrack was designed. After several game engines reviews, Unity was chosen because of its adaptability and convenience. PC was the selected platform for the design. The elements that are part of the soundtrack were created following audio production criteria for visual media. Unity was used for the implementation of these sound elements, in which a second design of performance was made. Mentioned performance was evaluated through a technical revision and a user survey of students in three representative high school establishments in Quito, so the contribution in the game to the user experience can be proven. The results point out some sound features that can be improved with better design tools, and show that soundtracks are fundamental factors that allow the user to get totally immersed in the world that the game creates.